Online art class: a study on the cause and effect of plagiarism - Riyan Hidayatullah; Susi Wendhaningsih (Universitas Lampung, 2021)
This study discusses the problem of plagiarism in art learning in online classes. The art class was conducted using the Learning Management System (LMS) and attended by 31 Pendidikan Anak Usia Dini (PAUD) students, and arts department. This research method uses a survey derived from two types of data. The first data was obtained from a questionnaire distributed to 211 art students. Factors that determine copy-paste occur because of the tendency to postpone tasks, so they work at the end of time. The following data comes from the discussion assignment report done by the student. Tasks are scanned online using the application. The results of the analysis of plagiarism showed an average of 49.09%, with a word similarity level of 80.77%. Based on online scan reports, the source of plagiarism comes from the university repository. Students use Open Educational Resource (OER) in the form of dictates as material for doing art lecture assignments. In conclusion, students mistakenly understood the use of OER and digital literacy. Digital-based arts learning does not have a significant impact and requires the provision of academic writing.Keywords: Art Learning, LMS, OER, Digital Literacy, Plagiarism